SYSTEMATIC LITERATURE REVIEW : SISTEM INFORMASI MANAJEMEN PENGELOLAAN EKSTRAKURIKULER BERBASIS WEB - Andrian; Ines Heidiani Ikasari (Journal of Research and Publication Innovation, 2023)
Technological development is growing rapidly in all aspects of life, one of which is in the field of education. There are several factors or aspects that contribute and support the possibility of scientific progress today. The presence of a technology-based system is one of the supporting factors. Extracurricular activities are non-educational activities held by schools or universities as a means for students to channel their interests and talents which are carried out outside of school hours. Therefore, a management information system must be implemented in a school for extracurricular management at school. This research aims to evaluate a web-based extracurricular management system whose data is collected from related journals in 2019-2023. In this study, researchers used the Systematic Literature Review (SLR) method. Systematic literature review (SLR) is one of the research techniques used to systematically collect, assess, and synthesise data from various articles or related scientific publications. To produce more objective and accountable results. This method searches for and selects relevant material using established procedures. searching for related articles using databases related to web-based extracurricular management. The results of this study indicate that the use of the Waterfall method on a web-based extracurricular management system has the most occurrences or is often used in the 2019-2023 period, this study also provides the advantages and disadvantages of several methods used to create a web-based extracurricular management system design and this study shows the research method that has the best results on a web-based extracurricular management system.